Biosécurité et surveillance épidémiologique - Valleron, Alain-Jacques (Comptes Rendus Biologies, 2024)
Biosecurity is a word including, in French, two concepts which are differently expressed in the English literature: the biosafety (to prevent accidental releases of infectious agents, for example, in research laboratories) and the biosecurity (to prevent the voluntary dispersion of infectious agents by bioterrorists, for example). Up to now, bioterrorism using a biological weapon has been very rare. Epidemiological surveillance is frequently seen as an efficient tool to achieve a better biosafety, and increase biosecurity. However, biosecurity requires an alert system. Traditional surveillance, which was developed to help to design the health policies, lacks the sensitivity and rapid response delay necessary for alert. Biology brings new opportunities for alert and surveillance. Examples are the monitoring of sewer systems and the development of CRISPR tools for detection of biological agents. A new problem is that these tools can be used out of the research laboratories, because they are relatively cheap and easy to develop. Finally, whatever the method used to identify quickly a new hazard, the key problem is the “preparedness” to identify and connect quickly the biomedical experts able to provide the best response to this hazard.